Khitanan Massal sebagai Bentuk Kepedulian terhadap Keluarga Kurang Mampu - Asmalinda, Wita; Sapada, Edy; Darma, Lidrian Arifan; Febriana, Nuke (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Circumcision as protection to prevent sexually transmitted diseases. The type of community service implemented is the Community Partnership Program (PKM) in the form of providing direct services to the community in the form of mass circumcision activities. This community service activity was carried out for 3 days which were used for preparation in the form of processing community service permits, preparing places, facilities and training tools, as well as consumption and lunch for participants and organizers of the mass circumcision activity. Of the 30 participants, all were circumcised well and smoothly. Evaluation was carried out by participants coming for a check-up at the Ibnu Sina Circumcision House. It can be concluded that this mass circumcision activity is very useful and its benefits are felt by the less fortunate surrounding community.